Reexamining and Reimagining the Future of Barangay (Village) Nagbalon: Solidarity Program and Community Based Enterprise Approaches for the Local Governance of the Sustainable Development Goals - Valenzuela, Victoria P.; Batac, Joseph H.; Parinas, Sherwin S. (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
The UN SDG for performance measures is already in place that makes the Barangay Solidarity Program build to address one of the issues which are ageism. In today’s changing society, not only changing values are important, but also changing the numbers and mindset of the people. Old persons have seen many changes in their lives, and the changes associated with aging are taken pretty much in stride. This study examines the real happiness of older persons, the expectations that society has for them, how people adapt to future forces in later life. The study employed a mixed-method approach. The successful aging dimensions were reviewed among older persons. A quantitative survey among 200 older persons and exploratory factor analysis was applied to test the structural validity of the instrument. This includes the ten dimensions of happiness namely: food, family, friends, faculty, fitness, financial, faith, future, and fear. In addition, this study explores that the older persons of the future may have no choice but to be self-reliant. The obtained results indicated that the happiness of older persons has significant effects on their faculty, faith, and future singly and in the combination of moderating variables such as age, gender, and pension. The different stakeholders' collaboration, co-production, and co-creation should be realized to meet the challenges on what the people feel, need, and get involved in their resilient bright future and capacity building as part of community-based enterprises. For future undertakings, other researchers may consider government organizations as co-leadership, and co-organizers of every barangay success for aging society, pandemic crisis and disaster preparedness, and economic enterprises at individual and social levels for sustainable development goals of local governance.